THE RELATIONSHIP OF COMPLIANCE IN CONSUMING FE TABLETS AND THE INCIDENT OF ANEMIA IN PREGNANT WOMEN IN THE TRIMESTER III - Veryudha Eka Prameswari (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: The type of anemia that often occurs in pregnancy is caused by a deficiency of iron (Fe) which can be called iron nutritional anemia. The incidence of anemia in pregnant women at PMB Diya Amanatur Rohmah is still relatively high, namely around 60%. Compliance is obedience to fulfill the recommendations of health workers without coercion. The low compliance with iron supplementation is supported by the percentage of compliance carried out by previous researchers. Of the 43 respondents who complied with consuming Fe tablets, there were 69.8% of respondents.Objective: This study aims to determine the relationship between adherence to consuming Fe tablets and the incidence of anemia in third trimester pregnant women. This research uses quantitative research methods. Method: This cross-sectional study involved pregnant women receiving care at BPM Diya Amanatur Rohmah, Kesamben, Jombang. A total of 34 respondents were selected through purposive sampling between January 8 and 30, 2023. Data collection was conducted using a compliance questionnaire, and analysis was performed using the chi-square test.Results: The results of the study used the chi-square test and obtained p-value = 0.000. Because the p-value < α (0.05), there is a relationship between adherence to consuming Fe tablets and the incidence of anemia in third trimester pregnant womenConclusion: Health workers can provide education about anemia by giving a health education about the benefits of Fe tablets and the importance of being obedient to consuming Fe